The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1161/01.str.15.6.1039
|View full text |Cite
|
Sign up to set email alerts
|

The profile of recovery from stroke and factors influencing outcome.

Abstract: The recovery from stroke of 154 survivors out of 255 stroke patients was analyzed. The outcomes documented were: discharge from hospital, activities of daily living (ADL) and return to work. A clear improvement in neurological and neuropsychological deficits was seen from the acute stage to three months, and this continued to twelve months, but to a lesser degree. 69% and 78% respectively, of the patients were at home three and twelve months after stroke. Independence in ADL increased from 32% acutely to 62% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
2
6

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(161 citation statements)
references
References 28 publications
(11 reference statements)
18
134
2
6
Order By: Relevance
“…The estimated completeness of case ascertainment in this population has been approximately 88% through a multinomial-logit capture recapture model 24 . Stroke severity at the time of maximum impairment was: 15.8%, 11.4% and 68.9% of patients had severe, moderate and mild unconsciousness [Glasgow coma scale (GCS) scores stratified into three: severe (3)(4)(5)(6)(7)(8), moderate (9)(10)(11)(12) and mild (13-15)] 19 , respectively; and 41.7% and 35.5% of patients had urinary incontinence and dysphagia, respectively. Structured questionnaires were used for initial registration and for follow-ups.…”
Section: Study Population Patient Notification and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated completeness of case ascertainment in this population has been approximately 88% through a multinomial-logit capture recapture model 24 . Stroke severity at the time of maximum impairment was: 15.8%, 11.4% and 68.9% of patients had severe, moderate and mild unconsciousness [Glasgow coma scale (GCS) scores stratified into three: severe (3)(4)(5)(6)(7)(8), moderate (9)(10)(11)(12) and mild (13-15)] 19 , respectively; and 41.7% and 35.5% of patients had urinary incontinence and dysphagia, respectively. Structured questionnaires were used for initial registration and for follow-ups.…”
Section: Study Population Patient Notification and Data Collectionmentioning
confidence: 99%
“…Stroke survivors have been reported as showing improvements in basic and instrumental ADL from stroke onset to 3 months and 1 year poststroke [6][7][8][9][10] . A number of studies have reported predictors of poor ADL at 3 months and 1 year post-stroke such as gender, age of stroke onset, marital status, living conditions, pre-stroke basic ADL, hemiparesis, motor impairment, urinary incontinence, visuoperceptual deficit, communication problem, intelligence/memory impairment and total anterior circulation infarction 8,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kapral ve ark. 'nın 2005 yılında yayınlanan çalışmalarında ise, kadın ve erkek strok hastalarında tedavi yaklaşımı arasında farklılık gösterilmemiştir (15). Altı aylık prognozda kadınlarda kötü prognozun minimal daha belirgin olduğu belirtilmiştir.…”
Section: Derleme Reviewunclassified
“…Many patients exhibit some spontaneous recovery of function following an ischemic brain lesion 33 . Resolution of tissue damage, including edema and inflammation, and spontaneous reperfusion can mediate recovery in the acute phase after a stroke 1,11 .…”
Section: Lesion-induced Plasticity and Functional Recoverymentioning
confidence: 99%